HIBRIDISASI KONSEP SAINS DAN EKSPRESI SENI DALAM EMBELAJARAN IPAS DI SD/MI: KAJIAN KONSEPTUAL DAN IMPLIKASI PEDAGOGIS - Lestari, Dyah Pranowo; Sunhaji, Sunhaji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This article aims to develop a conceptual framework for the hybridization between scientific concepts and artistic expression in IPAS learning at the elementary school level, as well as to examine its pedagogical implications. Using a conceptual review approach, this study synthesizes literature related to scientific representation, multimodal learning, art as a learning medium, and integrated approaches in primary education. The synthesis indicates that science–art hybridization enriches IPAS learning through four key dimensions: representation, experience, thinking processes, and expression. Art supports the transformation of abstract scientific concepts into concrete and multimodal forms, strengthens students’ emotional engagement, and integrates both analytical and divergent thinking processes. These findings carry important implications for IPAS instructional practices, particularly in strengthening multiple representations, enhancing learning engagement, fostering creativity, and creating inclusive learning environments aligned with the Merdeka Curriculum. This review also opens avenues for future research to empirically examine the effectiveness of the hybridization model in classroom settings,